“The Noise of Our Living”: Richard Wright and Chicago Blues - Jeff Wimble (Humanities, 2024)
Historicizing the musical genre known as “Chicago blues,” I further complicate Richard Wright’s already complicated attitudes toward “the folk” and modernity. Utilizing close readings of 12 Million Black Voices, I show how Wright’s apparent denigration of the blues as an outmoded, pre-modern artistic form is dependent on his historical situation writing before the advent of a new electrified form of blues that developed in Chicago shortly after the book’s publication. Utilizing biographical details of the life of Muddy Waters, I show how his work as a musician in Mississippi, then in Chicago, and his development of an electrified blues style, parallels and personifies the shift from an African American perspective rooted in an agrarian, pre-modern south to an industrial, modern north documented so effectively by Wright. Furthermore, the Chicago blues musicians’ transmogrification of the rural Delta blues into an electrified, urban expression manifests the vernacular-modernist artistic conception which Wright seems to be envisioning and pointing toward in 12 Million Black Voices.